Five Plant Natural Products Are Potential Type III Secretion System Inhibitors to Effectively Control Soft-Rot Disease Caused by Dickeya - Hu, Anqun; Hu, Ming; Chen, Shanshan; Xue, Yang; Tan, Xu; Zhou, Jianuan (Frontiers in Microbiology, 2022)
Dickeya zeae, a plant soft-rot pathogen, possesses a type III secretion system (T3SS) as one of the major virulence factors, infecting a wide variety of monocotyledonous and dicotyledonous plants and causing serious losses to the production of economic crops. In order to alleviate the problem of pesticide resistance during bacterial disease treatment, compounds targeting at T3SS have been screened using a hrpA-gfp bioreporter. After screening by Multifunctional Microplate Reader and determining by flow cytometer, five compounds including salicylic acid (SA), p-hydroxybenzoic acid (PHBA), cinnamyl alcohol (CA), p-coumaric acid (PCA) and hydrocinnamic acid (HA) significantly inhibiting hrpA promoter activity without affecting bacterial growth have been screened out. All the five compounds reduced hypersensitive response (HR) on non-host tobacco leaves and down-regulated the expression of T3SS, especially the master regulator encoding gene hrpL. Inhibition efficacy of the five compounds against soft rot were also evaluated and results confirmed that the above compounds significantly lessened the soft-rot symptoms caused by D. dadantii 3937 on potato, D. fangzhongdai CL3 on taro, D. oryzae EC1 on rice and D. zeae MS2 on banana seedlings. Findings in this study provide potential biocontrol agents for prevention of soft-rot disease caused by Dickeya spp.